Anti-vibration method for sensing ring of fiber optical current transformer integrating structural design and adaptive signal processing - Lin Cheng; Jianyong Luo; Weibin Si; Yanhua Han; Kun Zuo; Haitao Sun; Bo Niu; Shuangzan Ren (PLoS ONE, 2026)
This paper presents an in-depth study on vibration resistance improvement and fault identification technology for fiber-optic current transformers (FOCTs). The research analyzes the working principle of FOCTs, focusing on the Faraday magneto-optical effect and Ampere’s circuital law, alongside optoelectronic device models. The impact of vibration on FOCT performance is thoroughly investigated through theoretical analysis and experimental research, clarifying how vibration affects components like polarization-maintaining delay fiber and sensing fiber. Experimental studies on random and impact vibration characteristics summarize the variation patterns of transformer performance before and after vibration. To enhance vibration resistance and fault identification, corresponding measures are proposed using ANN-based and FIR filtering-based methods. These methods compensate for measurement errors under sinusoidal (semi-sinusoidal) and impact vibration conditions. The results demonstrate the effectiveness of these techniques in maintaining accurate current measurements despite vibrational interference. The findings provide a theoretical foundation and technical support for improving the operational stability of FOCTs in practical applications, particularly in harsh environments. This combined approach of optimized structural design and adaptive signal processing contributes to the advancement of FOCT technology and its wider adoption in demanding settings.